Lactobacillus paracasei KBL382 administration attenuates atopic dermatitis by modulating immune response and gut microbiota. Issue 1 (9th November 2020) - Kim, Woon-Ki; Jang, You Jin; Han, Dae Hee; Jeon, Kyungchan; Lee, Cheonghoon; Han, Hyuk Seung; Ko, GwangPyo
ABSTRACT: Administration of probiotics has been linked to immune regulation and changes in gut microbiota composition, with effects on atopic dermatitis (AD). In this study, we investigated amelioration of the symptoms of AD using Lactobacillus paracasei KBL382 isolated from the feces of healthy Koreans. Mice with Dermatophagoides farinae extract (DFE)-induced AD were fed 1 × 10 9 CFU d −1 of L. paracasei KBL382 for 4 weeks. Oral administration of L. paracasei KBL382 significantly reduced AD-associated skin lesions, epidermal thickening, serum levels of immunoglobulin E, and immune cell infiltration. L. paracasei KBL382-treated mice showed decreased production of T helper (Th)1-, Th2-, and Th17-type cytokines, including thymic stromal lymphopoietin, thymus, and activation-regulated chemokine, and macrophage-derived chemokine, and increased production of the anti-inflammatory cytokine IL-10 and transforming growth factor-β in skin tissue. Intake of L. paracasei KBL382 also increased the proportion of CD4+ CD25+ Foxp3+ regulatory T cells in mesenteric lymph nodes. In addition, administration of L. paracasei KBL382 dramatically changed the composition of gut microbiota in AD mice. Administration of KBL382 significantly ameliorates AD-like symptoms by regulating the immune response and altering the composition of gut microbiota.